A New Species of the Ponerine Ant Genus Myopias Roger from Yunnan, China, with a Key to the Known Oriental Species - Zheng-Hui Xu (Universidade Estadual de Feira de Santana, 2014)
A new species of the ponerine ant genus Myopias Roger, 1861 collected from southwestern China is described based on morphological features. M. daia sp. nov. is allied to M. luoba Xu & Liu, 2012, but differs from the latter by the shape of the posterior head margin, eye facet number, petiolar node shape, head sculpture, body color, and total length. The new species is also allied to M. nops Willey & Brown, 1983 and M. menba Xu & Liu, 2012, but differs from the latter two species by petiolar node shape, eye facet number, and body sculpture and color. A key based on the worker caste is provided to the eleven known Oriental species of the genus for the first time.